Sur les traces du Géant Patagon. L’histoire de la collection Henry de La Vaulx du musée du quai Branly (1896-1897) - Paz Núñez-Regueiro; Julio Vezub (Journal de la Société des Américanistes)
In the footsteps of the Patagonian Giant. The History of Henry de La Vaulx’s collection in the musée du quai Branly (1896-1897). The article summarises the results of a research project held by the authors since 2006. The project aimed to restore the historic coherence of a specific anthropological experience: that of the Henry de La Vaulx’s mission to Patagonia (1896-1897), that took place fifteen years after the Argentinean expansion to the Southern territories, controlled until then by the Mapuche and Tehuelche, or « Patagonians ». The material and documental records resulting from this mission were dispersed between several Parisian institutions after their arrival in France, and the project centers mainly on reconstructing its wholeness, through the observation and combined analysis of the artefacts that were allocated to the musée du quai Branly in 2004, the reading of the travel narrative, and the interpretation of the photographs and documentary corpus produced by the French explorer. After a discussion of the historiography which makes explicit the methodology, the article, at the crossing of ethnology, history and museum studies, presents the « colonial », « anthropological » and « ethnographic » dimensions of the collections, and raises the problem of the historicity of both narratives and objects in a context of crisis for the Patagonian populations.